Agrarian Conflict During the Administrative Process of Urban Spatial Planning in the Tegal Railway Station Area - Zuhairul Lathifah; Arif Zainudin; Agus Setio Widodo (PERSPEKTIF, 2026)
Agrarian conflicts arising from urban spatial planning have generally been examined from legal and land tenure perspectives, while limited attention has been given to how public administration processes shape unequal access to land and influence conflict resolution. This study addresses this gap by integrating Nancy Peluso’s Theory of Access and Dwight Waldo’s Public Administration Theory to analyze the administrative process of urban spatial planning, the interactions among institutional actors, and the mechanisms of agrarian conflict resolution in the Tegal Railway Station area. A qualitative case study approach was employed through in-depth interviews with representatives of PT Kereta Api Indonesia (Persero), the Tegal City Government, the National Land Agency (BPN), and Panggung Village, supported by court decisions and policy documents. The findings indicate that the conflict originated from overlapping claims between PT KAI’s historical grondkaart rights and the community’s long-term occupation since the 1950s. The administrative process was characterized by fragmented inter-agency coordination, limited participation of affected communities, and weak institutional integration, resulting in the prioritization of state asset protection over substantive conflict resolution. Although financial compensation was provided following the demolition of 22 buildings in March 2020, the legal status of the disputed land remained unresolved. The study contributes to the literature by demonstrating that agrarian conflicts in urban spatial planning should be understood not merely as legal disputes over land ownership but also as governance challenges involving unequal access to resources, institutional coordination, and democratic public administration. Strengthening participatory planning, legal certainty, and integrated inter-agency governance is therefore essential for achieving socially just and sustainable urban development.